Pupil Size Estimation Based on Spatially Weighted Corneal Flux Density - Yuning Zhang; Shuai Li; Jiang Wang; Ping Wang; Yan Tu; Xiaohua Li; Baoping Wang (IEEE Photonics Journal)
The pupil size is an important parameter in different studies on vision and ophthalmology. A pupil size estimation model is constantly needed when actual measurements are unavailable. The reported pupil estimation models commonly adopt the product of light intensity and viewing field area, supposing the light contributes uniformly across the spatial domain. In this paper, the pupil diameters were measured for stimuli with different intensities and different sizes. Spatially varying effect were observed, especially for large field stimuli and annular bright stimuli. A spatially weighted flux density is proposed which shows a high correlation with pupil diameters. A hyperbolic equation is fitted to estimate the natural pupil diameter with independent light spatial distributions. The goodness of fit R2 reaches 0.97. The accuracy of the model is further verified with a natural indoor scene for different viewing distances and different illumination levels. The model predicted pupil diameters show a high correlation with the measured data.